Efeito do treinamento de karatê combinado com intervenções multidisciplinares em adolescentes com sobrepeso e obesidade: um ensaio clínico randomizado - Souza, Fabricio de (2019)
Introduction: Several physical exercise interventions have been developed over time to benefit weight management and overall health in different populations. However, no studies using karate as an intervention for overweight and obese adolescents were found. Objective: To evaluate the effects of karate training combined with a nutritional and psychological intervention on body composition, anthropometric measures, inflammatory and lipid profile, oxidative stress, physical fitness, health conditions, quality of life, depression, and self-esteem for overweight and obese adolescents. Methods: A randomized, double-blind clinical trial was conducted on 70 overweight and obese adolescents attending six schools in the city of Tubarão, State of Santa Catarina, Brazil, between March and September 2018. A comparison was made between once-weekly nutritional and psychological intervention sessions and once-weekly nutritional and psychological intervention plus three karate training sessions per week. Sessions in both groups were one-hour long and lasted for 12 weeks. Assessments were made to identify levels of depression, self-esteem, health-related quality of life, and physical performance. In addition to anthropometric measurements, assessment was made of food intake, adverse treatment events, body composition, cardiometabolic risk factors, inflammatory markers, and oxidative stress. Results: A total of 90 adolescents were selected, of whom 70 were randomly assigned to one of the two groups. After the intervention period, the treatment group showed improvements in physical performance, body composition, health parameters, inflammatory markers, and oxidative stress. There were no significant adverse events derived from the interventions. Conclusion: The study concluded that intervention with karate training, combined with a nutritional and psychological intervention, proved to be effective in improving physical performance, body composition, health parameters, inflammatory markers, and oxidative stress in overweight and obese adolescents.